2020
DOI: 10.1126/science.abf5084
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine trial ethics once we have efficacious vaccines

Abstract: Some placebo-controlled trials can continue ethically after a candidate vaccine is found to be safe and efficacious

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 6 publications
0
41
0
1
Order By: Relevance
“…Now, with the approval of the first vaccines, placebo-controlled trials are considered unethical ( 49 ) and alternative designs using sound causal inference methods are required such as for example non-inferiority randomized trials ( 50 ) or randomized vaccination rollout (similar to an individual stepped wedge design) once vaccines have been approved ( 51 ). However, placebo-controlled trials may become again possible or even necessary in the future, if new, relevant questions arise, e.g.…”
Section: Major Lessons Learnedmentioning
confidence: 99%
“…Now, with the approval of the first vaccines, placebo-controlled trials are considered unethical ( 49 ) and alternative designs using sound causal inference methods are required such as for example non-inferiority randomized trials ( 50 ) or randomized vaccination rollout (similar to an individual stepped wedge design) once vaccines have been approved ( 51 ). However, placebo-controlled trials may become again possible or even necessary in the future, if new, relevant questions arise, e.g.…”
Section: Major Lessons Learnedmentioning
confidence: 99%
“…Traditional large-scale individual-randomized, placebo-controlled trials are the basis of modern clinical decision-making and remain the most efficient way to obtain reliable results for novel vaccines [29] , as long as the trial’s risk-benefit profile remains acceptable [30] . Since emergency-use authorization and conditional licensure are not full licensures, the WHO has suggested that it is ethically acceptable to continue the blinded follow-up of placebo recipients in existing studies and to continue to perform placebo-controlled trials in order to yield unbiased evidence for the next vaccine candidates [29] .…”
Section: Perspectivementioning
confidence: 99%
“…Investigators, regulators, and bioethicists have provided the scientific, regulatory, and ethical basis for guiding this discussion; 3 , 4 , 5 , 6 , 7 , 8 , 9 some have focused on the essential need to collect long-term safety and efficacy data from all phase 3 RCTs, 4 , 5 , 6 , 8 whereas others addressed the right of placebo recipients to be informed in a timely manner and be vaccinated with a deployed vaccine. 3 , 7 , 9 The US Food and Drug Administration Vaccines and Related Biological Products Advisory Committee held three meetings in late 2020, 10 , 11 , 12 which provided public discussions on the unprecedented challenges the world is facing in 2021.…”
Section: Introductionmentioning
confidence: 99%